MODEL HIDRODINAMIKA 2-D ARUS PASANG SURUT PERAIRAN TELUK YOSUDARSO, PAPUA - Fendry Yandi Samuel Mamengko (Jurnal Natural, 2008)
The pattern of two-dimension current in the Yosudarso Bay waters generated by 8 main components (M2,S2,N2,K1,O1,P1,Q1) of tide have been modeled using hydrodynamic model of Pricenton Ocean Model (POM). In the spring and neap conditions, when flood towards ebb, generally the currents move outward of the bay, with maximum magnitudes of 0.15 m/s and 0.14 m/s respectively. Meanwhile, when ebb towards flood, the currents move inward to the bay, with maximum magnitudes of 0.10 m/s and 0.09 m/s respectively. The generated-current velocities are relatively weak so that the Yosudarso bay waters is characterized as calm waters. This situation is also supported by the tidal range that less than 2 meters